Analisis Pengendalian Internal Piutang Pada PT. XYZ - Azizi, Ainur Rifqi; Akhirruddin, Anita (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The present study aims to analyse the correlation between an increase in past due receivables and potential weaknesses in receivables management. Such weaknesses have the capacity to disrupt cash flow and the company's profitability, resulting in difficulties in meeting financial obligations and the possibility of bankruptcy. The objective of this research is to conduct a comprehensive analysis of the policies, the management of receivables, and the effectiveness of internal control mechanisms for receivables at PT. The specific focus of this research is on the policies and practices related to receivables management at PT. The present study employs qualitative research methodologies. The results of this research indicate fluctuations in the number of receivables that are past due during the 2021-2023 period, with a peak of 62% in 2021, a decline to 43% in 2022, and a resurgence to 56% in 2023. The internal factors contributing to this phenomenon include the absence of a dedicated unit for receivables management and the absence of stringent sanctions for consumers who default on payments. Externally, new consumers have been observed to deliberately delay payment. The company has implemented measures to mitigate receivables that are past due, including conducting customer credit analysis prior to extending credit and providing payment reminders prior to the due date (D-7 and D-3). However, the efficacy of these measures has been limited. The implementation of an internal control framework for receivables, grounded in the principles of the COSO framework, acknowledges the need for comprehensive management of these financial obligations. However, the efficacy of this framework is undermined by inherent weaknesses that persist and require redress.